Evaluasi Kepuasan Pelaksanaan Hybrid Learning di Institut Teknologi Sepuluh Nopember - Vanda Kalista Dewi; Mukti Ratna Dewi (Politeknik Statistika STIS, 2022)
The number of cases of Covid-19 from time to time in several regions in Indonesia has decreased. This has influenced several educational institutions to implement new policies that were initially carried out full-online or offline, starting to switch to hybrid learning slowly. The research was conducted to see the level of student satisfaction, student responses, aspects and indicators that need more attention, which is analyzed using the sentiment analysis method, Importance Performance Analysis, and satisfaction index so that it can be used as a reference by ITS in formulating the implementation of hybrid learning programs in the future. The research that has been done shows that the level of student satisfaction in the application of hybrid offline is very satisfied and hybrid online is satisfied. The internet connection indicator (Wifi) used by ITS to support the lecture process on aspects of learning methods is a main priority that requires more attention and quality improvement in offline and online hybrid applications.